Pengembangan Teknologi ERP Modul Customer Relationship Management Studi Kasus Gudang ACC Sampit - Elma Tiana; Eka Prasetyaningrum (Journal of Computer System and Informatics (JoSYC), 2020)
ERP (Enterprise Resource Planning) is a concept for planning and managing company resources including funds, people, machines, spare parts, time, materials and capacities that have a wide influence from top management to operations in a company so that they can be optimally utilized for generate added value for all interested parties (stake holders) of the company. CRM is an integrated function that supports a company in the fields of marketing, sales and service, which can increase the value of customer satisfaction. With the increase in the value of customer satisfaction, the company's sales figures will increase.